Treatment of chronic low back pain in obese patients (Research, Society and Development, 2023)
Obesity is a pathological state resulting from excess body fat, this disease occurs when there is an imbalance between energy intake and energy expenditure. Excess adipose tissue causes several abnormal biochemical reactions in the body, making it an inflamed environment and a risk factor for many other pathological conditions, especially in the musculoskeletal system. The lumbar spine, as it performs the weight bearing function of the upper body, ends up being the region most affected by obesity, bringing, among many consequences, chronic pain and functional disability for the patient. Thus, this article aims to elucidate the treatment of chronic low back pain caused by the pathophysiological processes of obesity. For this, a literature review of a basic nature was developed, with a bibliographic and descriptive approach. Articles were selected according to publication date, keywords and cost. In this way, 94 articles were found, of this amount, according to the inclusion and exclusion criteria, for the final version, 17 bibliographical references were used to compose the discussion. In the discussion, the treatment of chronic low back pain is approached, first presenting the various modalities of conservative, non-pharmacological and associated pharmacological treatment, followed by invasive treatment and, finally, surgical approaches for chronic low back pain. It is concluded, then, from this article, that there is a broad therapeutic arsenal for the treatment of chronic low back pain, making it possible to choose the patient's therapy according to the severity of the condition, the capacity of the professional who is assisting and the costs involved.